2017
DOI: 10.1186/s12885-017-3111-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of immunohistochemistry with PCR for assessment of ER, PR, and Ki-67 and prediction of pathological complete response in breast cancer

Abstract: BackgroundProliferation may predict response to neoadjuvant therapy of breast cancer and is commonly assessed by manual scoring of slides stained by immunohistochemistry (IHC) for Ki-67 similar to ER and PgR. This method carries significant intra- and inter-observer variability. Automatic scoring of Ki-67 with digital image analysis (qIHC) or assessment of MKI67 gene expression with RT-qPCR may improve diagnostic accuracy.MethodsKi-67 IHC visual assessment was compared to the IHC nuclear tool (AperioTM) on cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 45 publications
1
66
2
3
Order By: Relevance
“…Surprisingly, there was no correlation between changes in survivin mRNA as assessed by qRT-PCR and changes in protein expression as assessed immunohistochemically. However, the semi-quantitative assessment of survivin expression by IHC may be less sensitive than qRT-PCR, as appears to be the case for several other measured targets in human cancer [60][61][62]. Despite our previous observations of significant reductions in proliferation and induction of apoptosis in canine lymphoma cells treated with EZN-3042 in vitro, [49] we observed no correlation between alterations in proliferation/apoptosis assessed immunohistochemically and changes in survivin mRNA expression.…”
Section: Discussioncontrasting
confidence: 66%
“…Surprisingly, there was no correlation between changes in survivin mRNA as assessed by qRT-PCR and changes in protein expression as assessed immunohistochemically. However, the semi-quantitative assessment of survivin expression by IHC may be less sensitive than qRT-PCR, as appears to be the case for several other measured targets in human cancer [60][61][62]. Despite our previous observations of significant reductions in proliferation and induction of apoptosis in canine lymphoma cells treated with EZN-3042 in vitro, [49] we observed no correlation between alterations in proliferation/apoptosis assessed immunohistochemically and changes in survivin mRNA expression.…”
Section: Discussioncontrasting
confidence: 66%
“…However, the Ki67 reduced staining in the OD group, suggested that the lower representation of alveolar epithelium was due to a reduced proliferation of epithelial cells. Such discrepancy between transcript and protein expressions was already reported with Ki67 in breast cancer . We also investigated Itgb1 expression because of its implication in mammary proliferation .…”
Section: Discussionmentioning
confidence: 72%
“…Such discrepancy between transcript and protein expressions was already reported with Ki67 in breast cancer. 49 We also investigated Itgb1 expression because of its implication in mammary proliferation. 50 In the OD group, epithelial Itgb1 expression did not differ from that seen in CD animals.…”
Section: Discussionmentioning
confidence: 99%
“…The bioinformatics analysis results, other than verified the correlation between IDH3a with GLUT1, also found the mild correlation between IDH3a with HK2, which was not consistent with immunohistochemistry study results. Previous studies also found the RNA expression did not always correlate with protein expression …”
Section: Discussionmentioning
confidence: 88%
“…Previous studies also found the RNA expression did not always correlate with protein expression. [30][31][32] Our study further explored the cellular mechanisms involved in IDH3a affecting glucose uptake. We identified key factors affecting glucose uptake in lung cancer cell, including GLUT1, HK2, and p-AKT.…”
Section: Du Et Almentioning
confidence: 99%